CD44 and associated markers in oral rinses and tissues from oral and oropharyngeal cancer patients. (July 2020) - Cohen, Erin R.; Reis, Isildinha M.; Gomez-Fernandez, Carmen; Smith, Drew; Pereira, Lutecia; Freiser, Monika E.; Marotta, Gia; Thomas, Giovana R.; Sargi, Zoukaa B.; Franzmann, Elizabeth J.
Highlights: Unique tissue staining patterns associated with salivary biomarkers in oral cancer. Direct association between high soluble CD44 and strong CD44 expression in tissue. Correlation between high protein in rinses and peripheral/mixed p16 in tissue. Poorer survival associated with higher soluble CD44 and protein in oral rinses. Abstract: Objectives: Oral and oropharyngeal squamous cell carcinoma (OOPSCC) is a debilitating disease. Salivary rinses contain soluble tumor markers including CD44 (solCD44) and total protein (TP) that may aid detection and prognosis of these aggressive tumors. Here we aim to examine the relationship between these salivary biomarkers and tissue markers p16 and CD44 and determine whether these markers can predict progression-free survival (PFS) and overall survival (OS). Materials and methods: Prospective study to update biomarkers using oral rinses and tissues from OOPSC patients enrolled between 2007 and 2012 at an academic tertiary referral center. 64 cases from a 300-subject case-control study with archived tissue for immunohistochemistry were included. Results: 82.8% were male, 84.4% were ever smokers, 70.3% had disease stage T3-T4, and 57.8% presented with nodal disease. Nineteen patients (25%) were p16 positive. The group with strong tissue CD44 expression in membrane and cytoplasm had higher levels of solCD44 (mean 10.73 ng/ml) than other groups (5.47 ng/ml) (p = 0.033). TP levels were significantly reduced in oral rinses from subjects with p16 universal gross tumor tissue staining (mean 0.80 vs. 1.08 mg/ml; p = 0.039). On multivariate analysis, universal CD44 gross tissue staining and TP levels ≥ 1 mg/ml demonstrated poorer PFS, with the latter also affecting OS. Poorer survival was associated with soluble CD44 ≥ 5.33 ng/ml and TP ≥ 1 mg/ml. Conclusions: Direct associations were found between high solCD44 levels and strong membrane and cytoplasmic CD44 expression, and between high TP levels and peripheral/mixed p16 gross staining. Poorer PFS and OS are significantly associated with higher levels of solCD44 and protein in oral rinses.